1996
DOI: 10.1177/02841851960373p298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transurethral Microwave Thermotherapy

Abstract: The study does not support the view that TUMT leads to significant necrosis in the prostate with loss of tissue and retraction. We theorize that the response to TUMT may be caused by a denervation of the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The mechanism of TUMT comprises a coagulative necrosis of prostate tissue, which is later absorbed due to an inflammatory process of healing and shrinkage. Nordenstam et al [11] did not find considerable intraprostatic necrosis in their patients after treatment with lowenergy TUMT. However, several studies [12Á14] using high-energy protocols and ultrasound assessment of prostate size have described a significant reduction in prostate volume, ranging from 14% to 30%, at 6 months after TUMT.…”
Section: Discussionmentioning
confidence: 70%
“…The mechanism of TUMT comprises a coagulative necrosis of prostate tissue, which is later absorbed due to an inflammatory process of healing and shrinkage. Nordenstam et al [11] did not find considerable intraprostatic necrosis in their patients after treatment with lowenergy TUMT. However, several studies [12Á14] using high-energy protocols and ultrasound assessment of prostate size have described a significant reduction in prostate volume, ranging from 14% to 30%, at 6 months after TUMT.…”
Section: Discussionmentioning
confidence: 70%
“…MRI of the prostate soon after TUMT was particularly useful as it clarified the effect of TUMT on the prostate. Nordenstam et al [23] showed that low‐energy TUMT induce only an increase in the T2‐weighted signal, with no evidence of necrosis. However, a well‐defined area of perfusion defect in the central zone of the prostate on enhanced T1‐weighted images is a constant feature after high‐energy TUMT [24].…”
Section: Discussionmentioning
confidence: 99%